The past, present and future of shareholder activism by hedge funds - Cheffins, B; Armour, J (University of Iowa College of Law, 2011)
The forthright brand of shareholder activism hedge funds deploy emerged by the mid-2000s as a major corporate governance phenomenon. This Article explains the rise of hedge fund activism and offers predictions about future developments. The Article begins by distinguishing the "offensive" form of activism hedge funds engage in from "defensive" interventions "mainstream" institutional investors (e.g. pension funds or mutual funds) undertake. Variables influencing the prevalence of offensive shareholder activism are then identified using a heuristic device, "the market for corporate influence." The rise of hedge funds as practitioners of offensive shareholder activism is traced by reference to the "supply" and "demand" sides of this market, with the basic chronology being that, while there were direct antecedents of hedge fund activists as far back as the 1980s, hedge funds did not move to the activism forefront until the 2000s. The Article brings matters up-to-date by discussing the impact of the recent financial crisis on hedge fund activism and draws upon the market for corporate influence heuristic to predict that activism by hedge funds is likely to remain an important element of corporate governance going forward.